Phylogeography, colouration, and cryptic speciation across the Indo-Pacific in the sea urchin genus Echinothrix - Simon E. Coppard (Nature Portfolio, 2021)
Abstract The sea urchins Echinothrix calamaris and Echinothrix diadema have sympatric distributions throughout the Indo-Pacific. Diverse colour variation is reported in both species. To reconstruct the phylogeny of the genus and assess gene flow across the Indo-Pacific we sequenced mitochondrial 16S rDNA, ATPase-6, and ATPase-8, and nuclear 28S rDNA and the Calpain-7 intron. Our analyses revealed that E. diadema formed a single trans-Indo-Pacific clade, but E. calamaris contained three discrete clades. One clade was endemic to the Red Sea and the Gulf of Oman. A second clade occurred from Malaysia in the West to Moorea in the East. A third clade of E. calamaris was distributed across the entire Indo-Pacific biogeographic region. A fossil calibrated phylogeny revealed that the ancestor of E. diadema diverged from the ancestor of E. calamaris ~ 16.8 million years ago (Ma), and that the ancestor of the trans-Indo-Pacific clade and Red Sea and Gulf of Oman clade split from the western and central Pacific clade ~ 9.8 Ma. Time since divergence and genetic distances suggested species level differentiation among clades of E. calamaris. Colour variation was extensive in E. calamaris, but not clade or locality specific. There was little colour polymorphism in E. diadema.